Studies in leading and organizing schools - Hoy, Wayne (Information Age Publishing ( IAP ), 2003)
This volume provides a mix of beginning and established scholars and a range of theoretical perspectives. Eight separate but related analyses were selected for publication this year. The book begins with a chapter by Sims and Miskel, which examines national reading policy as part of a broader federal government agenda on children’s literacy. Using a model of punctuated equilibrium, they trace the peaks of congressional and media attention to literacy. Their findings reveal that the broad level of literacy has remained a rather active and durable policy issue for more than three decades. When, however, the analysis shifts to different targets, that is, from elementary and secondary school students to adults and youth to LEP individuals, there are distinct patterns of punctuation and equilibrium. The researchers conclude that the specific issue of children’s literacy in the 1990s is the latest version or episode of literacy policy produced by shifting images and venues.